A low-cost power management system design for residential hydrogen & solar energy based power plants - Bayrak, Zehra Ural; Bayrak, Gokay; Ozdemir, Mahmut Temel; Gencoglu, Muhsin Tunay; Cebeci, Mehmet (Pergamon-Elsevier Science Ltd, 2016)
This study focuses on developing a low-cost power management system for residential solar hydrogen power plants. The proposed power management system is designed as a hybrid control system consisting of a microcontroller and a Labview data acquisition card. Most of the controllers have some boundaries for power management, and providing a practical solution for hybrid power plants has some limitations. The proposed controller checks the total energy demand of the hybrid power plant in real time and operates the solar/hydrogen energy based power plant for the local load. The implemented electronic control card monitors the hybrid system and operates the related switches to select the proper energy source for the local load. The proposed real-time management system also provides a low-cost power management for the residential power plants, and the experimental results prove that the developed hybrid power management system is easy to implement and is suitable for residential applications. (C) 2016 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
3rd European Conference on Renewable Energy Systems (ECRES) -- OCT 07-10, 2015 -- Kerner, TURKEY
Keywords: Power management system; Residential hybrid power plant; Hydrogen energy; Solar energy; Sustainable energy